PTH-028 Is Flexible Sigmoidoscopy ever Enough? an Audit of the Rates of Proximal Disease During Colonoscopy. (4th June 2013) - Macdonald, S; Radhakrishnan, S; Seward, E
Abstract : Introduction: There is debate about appropriate initial endoscopic investigation of patients with symptoms suggestive of colorectal cancer. Thompson (2008) proposed that for patients without iron deficiency anaemia or abdominal mass; Flexible Sigmoidoscopy (FS) should be first line with further colonoscopy only if significant distal colonic disease was detected. A proximal cancer miss rate of 1:500 patients over 60 years and 1:3000 below this age was reported. It was argued that this approach would significantly reduce costs and burden on patients. However Lieberman (2000) reported 2.7% of asymptomatic patients screened with colonoscopy had proximal neoplasms without distal disease. We have applied the Thompson criteria to our unit's colonoscopy data to establish the rate of disease, both neoplastic and other, proximal to the splenic flexure which would have been missed by performing FS alone. Methods: All colonoscopies performed in our unit over 2 months were examined and those which met the Thompson criteria for FS were included. The procedure and pathology reports were reviewed and the number with proximal but without distal disease, and type of pathology was established. Adenoma with low grade dysplasia (LGD) was the minimum classification for neoplasm. Results: 342 colonoscopies were reviewed and 200 met the Thompson criteria for FS. 17 (8.5%) patients had proximal disease without distal disease, of which 9 (53%) were neoplastic and 8 (47%) had significant other disease (87.5% inflammatory). Of the 82 patients > 60 years, it was found that 10 (12.1%) had significant disease, of which 8 (80%) were neoplastic (6 tubular adenoma with LGD, 2 tubulovillous adenoma with LGD). Of the 118 < 60 years, 7 (5.9%) had significant disease (85% inflammatory) and 1 (15%) neoplastic. Conclusion: 4.5% of patients who would have had a FS using Thompson criteria were found to have a proximal neoplasm. This is considerably higher than initially reported and more in keeping with data from colonoscopic bowel screening. When examined by age, nearly 1:10 patients over 60 years would have had a missed proximal neoplasm. This rate was 1:100 for those who were under 60 years. A considerable volume of proximal non-neoplastic disease, mainly inflammatory, would also be missed with FS examination (1:20 patients under 60 years). This study supports the use of colonoscopy for first line investigation of all patients with symptoms suggestive of colorectal cancer. Disclosure of Interest: None Declared. References: Lieberman MD, Weiss DG, Bond JH, et al. Use of colonoscopy to screen asymptomatic adults for colorectal cancer. The New England Journal of Medicine 2000; 343: 162–168. Thompson MR, Flashman KG, Wooldrage K, et al. Flexible sigmoidoscopy and whole colonic imaging in the diagnosis of cancer in patients with colorectal symptoms. British Journal of Surgery ; 95:1140–1146.